PENGARUH BRAND IMAGE DAN HARGA TERHADAP KEPUASAN KONSUMEN AQUA MELALUI KEPUTUSAN PEMBELIAN DI SUPERMARKET HARI–HARI KOTA DUMAI RIAU - Handoyo, Teguh Tri (Prodi Magister Manajemen Universitas Wijaya Putra, 2024)
This research aims to determine the influence of brand image and price on consumer satisfaction at Hari - Hari Dumai City Riau Supermarket through intervening variables in purchasing decisions. This research uses a quantitative method with an explanatory research type. The sample in this study was taken as many as 100 people using accidental sampling technique. Hypothesis testing was carried out using a Structural Equation Model (SEM) approach based on Partial Least Square (PLS) using the SmartPLS version 3 application to test the relationship between variables. The research results show that brand image has an insignificant positive influence on Aqua purchasing decisions at the Hari - Hari Dumai City Riau Supermarket. Price and brand image have significant positive influence on Aqua purchasing decisions at the Hari - Hari Dumai City Riau Supermarket. Price does not have a significant effect on Aqua consumer satisfaction at Hari - Hari Dumai City Riau Supermarket. Purchasing decisions have a significant effect on Aqua consumer satisfaction at Hari - Hari Dumai City Riau Supermarket. Brand image has an insignificant indirect effect on Aqua consumer satisfaction through purchasing decisions at the Hari - Hari Dumai City Riau Supermarket. Price has an indirect effect on Aqua consumer satisfaction through purchasing decisions at the Hari - Hari Dumai City Riau Supermarket.